Eine kritische Betrachtung des Diversitätsproblems in Banken: Ursachen und Erfolgsstrategien zur Steigerung des Frauenanteils in Führungspositionen - Marcel Dulgeridis; Elisabeth Dewaldt; Sabrina Dulgeridis (IU Internationale Hochschule, 2024)
This paper explores the reasons behind the underrepresentation of women in leadership positions in the banking sector. Despite women making up a significant portion of the workforce, their presence in top management roles remains limited, affecting the sector's performance and competitiveness. The analysis highlights the importance of promoting women in leadership for both societal and economic progress. Key barriers include historical inequalities, unconscious biases, a lack of female role models, structural obstacles, and challenges in balancing career and family life. Existing initiatives by cooperative banks, savings banks, and large commercial banks to support women are reviewed, showing mixed progress. The paper proposes actionable recommendations for creating a more inclusive corporate culture, breaking down gender barriers, and enhancing equal opportunities. This includes promoting flexible work arrangements, transparent promotion processes, targeted development programs, and the use of AI-based tools to ensure gender equity. Ultimately, fostering gender diversity in leadership is crucial for building a fairer and more inclusive society and for improving the overall performance of the banking sector.
Keywords: 650; Gender Diversity; Leadership Barriers; Corporate Culture and Inclusion; Role Models; Leadership Development Strategies; Unconscious Bias; Structural Barriers; Work-Family Balance; Flexible Work Models; Gender Equity Tools; Mentoring and Networking; Financial Sector Trends; Technological Innovation in HR; Women Empowerment; Organizational Change